CCRI Sample Designs and Sample Point Identification, Data Entry, and Reporting (SPIDER) Software. - Darroch, Gordon; Smith, Richard D. B.; Gaudreault, Michel (Historical Methods)
The Canadian Century Research Infrastructure (CCRI) began with the development of designs for large representative samples of the decennial census from 1911 to 1951 and continued with the development of sophisticated SPIDER software for data entry and processing. This work builds on previous research projects in several ways, including the use of digital images within an integrated suite of Java-based software programs. By describing the theoretical and practical questions addressed in the CCRI initiative, the authors seek to contribute to international efforts to enhance construction of historical databases for systematic research on economic, social. and political change.